3y^2 - 192 = 0
First: find the greatest common factor (find a number divisible by the coefficients) > break each term into lowest terms >
3(y)(y) - 3(4)(4)(4) = 0
3(y^2 - 64) = 0
Sec: factor the term in the parenthesis :
3(y + 8)(y - 8) = 0
Third: solve for the "y" variables > set both parenthesis to equal "0" >
y + 8 = 0
y + 8 - 8 = 0 - 8
y = - 8
y - 8 = 0
y - 8 + 8 = 0 + 8
y = 8
y = - 8 and 8
2007-01-07 04:53:34
·
answer #1
·
answered by ♪♥Annie♥♪ 6
·
1⤊
0⤋
3 y 2 - 192 = 0
3(y^2 - 64) = 0
3(y-8)(y+8)=0
y-8 = 0 so y = 8
y+8 = 0 so y = -8
2007-01-07 12:48:23
·
answer #2
·
answered by ironduke8159 7
·
1⤊
0⤋
factor out the 3
3(y^2 - 64) = 0
Difference of squares
3(y - 8) (y + 8) = 0
Solve for y.
y - 8 = 0 and y + 8 = 0
y = 8 and -8
2007-01-07 12:47:01
·
answer #3
·
answered by OSO 3
·
1⤊
0⤋
divide out the 3 so u have y^2 - 64 = 0.
now
(y-8)(y+8) = 0
y = +/- 8
2007-01-07 12:45:54
·
answer #4
·
answered by venusvakhshori 2
·
1⤊
0⤋
3y^2 - 192 = 0
3y^2 = 192
y^2 = 64
therefore y = +8 or y = -8
2007-01-07 12:45:11
·
answer #5
·
answered by Neelu 2
·
1⤊
0⤋
3(y^2-64)=0
(y+8)(y-8)=0
y=±8
2007-01-07 12:47:28
·
answer #6
·
answered by Anonymous
·
1⤊
0⤋